Feminine imagery in Gnostic-Christian literature - Cerioni, Lavinia (2019)
This thesis investigates the use of feminine as an intellectual category in Gnostic mythologies. In particular, it shows what aspects of God Gnostic theologians intended to convey through feminine imagery.